1434 Rebuilding a concept for the periodical health examination in japan. (24th April 2018) - Okubo, Yasushi; Kuroda, Reiko; Yamamoto, Kenya
Abstract : Introduction: The aims of the periodical health examination have been changed in accordance with social conditions and necessities in the ages. In past, the main aim was the prevention the occupational disease and work-related disease. In recent years, they are the prevention the metabolic syndrome and cardiac or cerebrovascular diseases. However, it is unclear the next step. Therefore, we investigated a concept of the periodical health examination for workers. Methods: We conducted reviews on the usability of the items of the periodical health examination and focus group discussions with the professional occupational health physicians. The first procedure was reviews of the items of the periodical health examination. The second procedure was the focus group discussion on the usability of the periodical health examination. Then we classified the issues into 5 groups. Each group made a concept of the health examination by focus group discussion. Results: Most of the items of the health examination were not effective to predict the onset the disease by the results of the literature reviews. However most of the occupational health physicians utilised each item in the health management activities. As the results of the focus group discussions, it was pointed out that the development the productivities and reduction the accidents at work should be adopted in the aims in the future, the fitness at work and the improvement the workers' health literacy should be used as the outcome, the prevention the cancers should be conducted as not the screening but the risk assessment. Conclusion: The health examination until now is the screening of the target diseases, but it should be developed into the evaluation the risk of the disease and working conditions, and the aims should be not only the workers' health but the development the productivities and the workers' health literacy.